Interactions between tetrathiafulvalene units in dimeric structures – the influence of cyclic cores - Jiang, Huixin; Mazzanti, Virginia; Parker, Christian R.; Broman, Søren Lindbæk; Wallberg, Jens Heide; Lušpai, Karol; Brincko, Adam; Kjaergaard, Henrik G.; Kadziola, Anders; Rapta, Peter; Hammerich, Ole; Nielsen, Mogens Brøndsted (Beilstein Journal of Organic Chemistry, 2015)
A selection of cyclic and acyclic acetylenic scaffolds bearing two tetrathiafulvalene (TTF) units was prepared by different metal-catalyzed coupling reactions. The bridge separating the two TTF units was systematically changed from linearly conjugated ethyne, butadiyne and tetraethynylethene (trans-substituted) units to a cross-conjugated tetraethynylethene unit, placed in either acyclic or cyclic arrangements. The cyclic structures correspond to so-called radiaannulenes having both endo- and exocyclic double bonds. Interactions between two redox-active TTF units in these molecules were investigated by cyclic voltammetry, UV–vis–NIR and EPR absorption spectroscopical methods of the electrochemically generated oxidized species. The electron-accepting properties of the acetylenic cores were also investigated electrochemically.
Keywords: alkynes; mixed valence; radiaannulene; tetraethynylethene; tetrathiafulvalene